An Image of Who We Might Become: Vision Communication, Possible Selves, and Vision Pursuit - Stam, Daan; Lord, Robert G.; Knippenberg, Daan van; Wisse, Barbara (Organization Science, 2014)
We propose a model of vision communication that emphasizes the mediating role of follower collective possible selves—that is, self-conception in terms of what the collective (team, organization) which one is a member of may become in the future that can be held by individuals but can also be shared by multiple individuals. Our model is the first to provide an integrative account of how vision communication may stimulate the pursuit of the vision by individuals and collectives, and it complements and extends prior research in three important ways. First, in contrast to an earlier emphasis on the role of individual perceptions of the current self, our model puts perceptions of the future self at the forefront. It captures how vision communication can invite social sharedness of these perceptions, thus doing justice to visions’ nature as images of a future for the collective. Second, in contrast to earlier work on vision communication focusing on general indicators of leadership effectiveness, our model puts what is arguably the most important outcome for vision communication center stage: vision pursuit, the followers’ actions aimed at making the vision reality. We argue that the creation of collective possible selves by followers is crucial for vision communication because collective possible selves explain how vision communication relates to vision pursuit. Third, our model also addresses aspects of vision communication that may facilitate the processes through which visions become internalized as possible selves, and it captures the processes through which such possible selves become shared among members of a collective and lead to collective vision pursuit.